Answer:
The 10th term will be:
[tex]a_{10}=\frac{1}{512}[/tex]
Step-by-step explanation:
Considering the sequence
[tex]1,\:\frac{1}{2},\:\frac{1}{4}...[/tex]
A geometric sequence has a constant ratio r and is defined by
[tex]a_n=a_0\cdot r^{n-1}[/tex]
[tex]\mathrm{Compute\:the\:ratios\:of\:all\:the\:adjacent\:terms}:\quad \:r=\frac{a_{n+1}}{a_n}[/tex]
[tex]\frac{\frac{1}{2}}{1}=\frac{1}{2},\:\quad \frac{\frac{1}{4}}{\frac{1}{2}}=\frac{1}{2}[/tex]
[tex]\mathrm{The\:ratio\:of\:all\:the\:adjacent\:terms\:is\:the\:same\:and\:equal\:to}[/tex]
[tex]r=\frac{1}{2}[/tex]
[tex]\mathrm{The\:first\:element\:of\:the\:sequence\:is}[/tex]
[tex]a_1=1[/tex]
[tex]\mathrm{Therefore,\:the\:}n\mathrm{th\:term\:is\:computed\:by}\:[/tex]
[tex]a_n=\left(\frac{1}{2}\right)^{n-1}[/tex]
Putting n = 10 to determine in the nth term to determine the 10th term
[tex]a_{10}=\left(\frac{1}{2}\right)^{10-1}[/tex]
[tex]a_{10}=\left(\frac{1}{2}\right)^9[/tex]
[tex]\mathrm{Apply\:exponent\:rule}:\quad \left(\frac{a}{b}\right)^c=\frac{a^c}{b^c}[/tex]
[tex]a_{10}=\frac{1^9}{2^9}[/tex]
[tex]a_{10}=\frac{1}{2^9}[/tex] ∵ [tex]1^9=1[/tex]
[tex]a_{10}=\frac{1}{512}[/tex] ∵ [tex]2^9=512[/tex]
Therefore, the 10th term will be:
[tex]a_{10}=\frac{1}{512}[/tex]